EduTales: an educational comic to support students’ learning experience at the Centre for Foundation Studies, IIUM - Azrymi, Amirul Nazmi; Shuhaimi, Azwa Safrina; Kamaruzaman, Amanati Saffiyah; Mohd Adli, Muhammad Adam; Fahrizal, Muhammad Faris; Ahmad Kamal, Nur Nabila (Centre of Foundation Studies, UiTM, 2024)
Many students at this level struggle to engage with standard educational resources, emphasizing the need for innovative tools to improve comprehension of course contents. This study introduces EduTales, an education supplemental tool tailored for foundation-level students, aiming to address the challenge of disengagement with traditional course materials. For this, EduTales leverages the inherent appeal of comics to create an engaging learning experience. Through incorporating interesting characters, scenes, and storylines, EduTales’s objective is to enhance students' understanding of their course contents while ensuring enjoyable learning experience through appealing pictures, conversational delivery, and interesting storylines. It provides learners with crucial contexts for understanding the essence of the subjects, as well as delivering exciting backgrounds and clear graphics to make the plot easy to understand. To assess the effectiveness of EduTales, two instruments are employed to gather efficacy data, namely Pre-Test and Post-Test, as well as a survey to gauge feedback on the innovation. Then, the scores are consolidated in a bar chart format to show the changes between the pre-test and post-test. The findings indicate a positive response from students, who found EduTales both engaging and helpful for understanding complex topics - even surpassing initial expectations. Additionally, EduTales’s availability in both online and flip-book formats proved to be popular among students, suggesting its potential for broader usage and commercial success. By offering EduTales to other universities, educators can provide students with an effective tool to improve comprehension and engagement. In conclusion, EduTales provides major benefits, including improved comprehension, ease of access, and the usage of relatable lexicons for the youth, making it a versatile and valuable resource for enhancing educational outcomes in modern learning environments.